The D-Property of Finite Unions of t-Metrizable Spaces and Certain Function Spaces. (13th November 2013) - Zhang, Xin; Guo, Hongfeng
Abstract : The additivity of D -property is studied on t -metrizable spaces and certain function spaces. It is shown that a space of countable tightness is a D -space provided that it is the union of finitely many t -metrizable subspaces, or function spaces C p ( X i ) where each X i is Lindelöf Σ .